Omaha Beach : V Corps battle for the beachhead - Kilvert-Jones, Tim. (Barnsley, South Yorshire : Cooper ; Conshohocken, Penn. : Combined Pub., 1999)
This book guides the reader through the battle for the V Corps beachhead, the fiercest and bloodiest of the Landings. Events from the early stages of planning Operation Neptune-Overlord through to the battles between 6 to 8 June 1944 are examined.
The second front -- Overlord assault plan : Omaha Beach and Pointe du Hoc -- The invasion -- Tour A : D-Day -- Rangers at Pointe du Hoc -- Tour B-1 : D-Day -- 29th Division's units at Omaha Beach -- Tour B-2 : D-Day -- the assault by the 1st Dvision -- Epilogue : at the going down of the sun.
Includes bibliographical references (page 179) and index.
Keywords: United States. -- Army. -- Infantry Division, 1st.; 1939-1945; World War, 1939-1945 -- Battlefields -- France -- Normandy -- Guidebooks; Battlefields; Military campaigns; travel guidebooks; Guidebooks; Military history; Guidebooks; Guides touristiques